2013
DOI: 10.1016/j.brat.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Referral for psychological therapy of people with long term conditions improves adherence to antidepressants and reduces emergency department attendance: Controlled before and after study

Abstract: BackgroundReferral to psychological therapies is recommended for people with common mental health problems (CMHP) however its impact on healthcare utilisation in people with long term conditions (LTCs) is not known.MethodRoutinely collected primary care, psychological therapy clinic and hospital data were extracted for the registered population of 20 practices (N = 121199). These data were linked using the SAPREL (Secure and Private Record Linkage) method. We linked the 1118 people referred to psychological th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…The low-intensity service typically offered brief courses for people with mild and moderate anxiety or depression, mostly by telephone, but face-to-face and computer-based support was available. Published evaluations have reported recovery rates in excess of 50%, supporting service objectives, and IAPT is now developing services to provide tailored support for people with mental health needs associated with a long-term physical condition [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The low-intensity service typically offered brief courses for people with mild and moderate anxiety or depression, mostly by telephone, but face-to-face and computer-based support was available. Published evaluations have reported recovery rates in excess of 50%, supporting service objectives, and IAPT is now developing services to provide tailored support for people with mental health needs associated with a long-term physical condition [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Through continuous quality improvement efforts at the national, state, and clinic level, the national average for the depression CQM has increased from 38.8% in 2014 to 66.2% in 2017 in HCs as shown by Fig 1. Optimization of clinical workflow and health IT infrastructure also holds the potential to enhance HC primary care teams' capacity in providing timely and high quality care. Effective care management through incorporation of patient health education, patient engagement in treatment and social services supports, as well as appropriate evidence-based pharmacotherapy or psychotherapy in the treatment of patients with chronic diseases and depression have been associated with increased use of antidepressants, reduced utilization of emergency services, and improved patient outcomes [38][39][40][41].…”
Section: Plos Onementioning
confidence: 99%
“…Among female HC patients of reproductive age, the prevalence of SPD is over 300% greater than the general population, which further underscores the importance of supporting primary care behavioral health integration in HC to address patients' behavioral health needs. Studies have demonstrated that the presence of SPD is associated with increased mortality, activity limitation, and decreased health-related quality of life[38][39][40]. The disproportionate prevalence and mental health burden of SPD among HC patients illustrates the…”
mentioning
confidence: 99%
“…The use of routine measurement of clinical outcomes in IAPT services has led to a large volume of research on outcomes in routine practice. Data from the initial demonstration sites have led to publications on clinical outcomes (Clark et al 2009 ; Richards and Borglin 2011 ), attendance (Di Bona et al 2014 ), cost-effectiveness (Mukuria et al 2013 ) and the wider impact of this service delivery model on hospital admissions, use of antidepressants and return to work (de Lusignan et al 2012 , 2013 ). Further multi-site IAPT datasets have been used to report service-level performance indicators (e.g.…”
Section: The Improving Access To Psychological Therapies (Iapt) Progrmentioning
confidence: 99%